Carbonization Process of Water Hyacinth as an Alternative Renewable Energy Material for Biomass Cook Stoves Applications. (February 2019) - Maulina, Wenny; Kusumaningtyas, Rani; Rachmawati, Zakiyah; Supriyadi,; Arkundato, Artoto; Rohman, Lutfi; Purwandari, Endhah
Abstract: Water hyacinth is a source of biomass, easily found in large quantities from our environment and one of renewable energy sources. As for biomass fuel, it was prepared by carbonizing process. Carbonization of biomass (fueling) includes a process to increase the content of heating value of biomass. In this study, carbonization process was carried out for temperatures 400oC, 500oC and 600oC. Activated carbons were prepared from water hyacinth using NaOH activation (ACWH). Characterization of the ACWH were performed using Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX), Fourier Transform Infrared Spectroscopy (FTIR) and X-ray Diffraction (XRD). Other physical parameter such as moisture content, ash content and volatile matter were measured in this article. The result of SEM-EDX showed the pore size and element carbon of the ACWH increases with increasing carbonization temperature. The ACWH was containing functional groups representing phenols, hydroxyl, carboxyl and carbonyl groups. The increases carbonization temperature seems to be increasing crystallinity and crystal size of the ACWH. The physical parameter of the ACWH showed ash content increases when increasing the carbonization temperature. Nevertheless, parameter of moisture content and volatile matter was decreased. The study concludes that the carbonization temperature of the ACWH causes changes in the characteristics of the structure and composition of chemical compounds which are different from the origin.